Polyethyleneimine modification of aluminum hydroxide nanoparticle enhances antigen transportation and cross-presentation of dendritic cells - Dong H (Dove Medical Press, 2018)
Heng Dong,1,2,* Zhi-Fa Wen,2,3,* Lin Chen,1 Na Zhou,1 Hui Liu,1 Shiling Dong,1 Hong-ming Hu,2 Yongbin Mou11Central Laboratory, Nanjing Stomatological Hospital, Medical School of Nanjing University, Nanjing, China; 2Laboratory of Cancer Immunobiology, Robert W Franz Cancer Research Center, Earle A Chiles Research Institute, Providence Cancer Center, Portland, OR, USA; 3Department of Microbiology and Immunology, Medical School of Southeast University, Nanjing, China*These authors contributed equally to this workBackground: The aim of this study was to explore the feasibility of delivering tumor antigens and enhancing the antigen cross-presentation of dendritic cells (DCs) by aluminum hydroxide nanoparticle with polyethyleneimine (PEI) modification (LV@HPA/PEI). Materials and methods: The LV@HPA nanoparticles were modified by PEI first, then the influence of LV@HPA/PEI on DCs was examined. The distinct expression of ovalbumin (OVA) protein transported into DCs by LV@HPA/PEI was observed by flow cytometry and Western blot. The biocompatibility of LV@HPA/PEI, maturity and antigen cross-presentation of DCs was observed in vitro. Tumor derived autophagosomes (DRibbles) combined with LV@HPA/PEI were loaded into DCs, and DC vaccines were used to immunize mice. The percentage of CD3+CD8+IFN-γ+ T cells in immunized mice was determined by flow cytometry. Additionally, the functional properties of the LV@HPA/PEI-DRibble-DCs vaccine were examined in vivo in PancO2 tumor-bearing mice.Results: In our study, we described how LV@HPA/PEI can be a functionalized antigen delivery system with notable antigen transport effect and negligible cytotoxicity. It was found that LV@HPA/PEI could be easily internalized into DCs to assist antigen release into the cytoplasm. In addition, DCs matured gradually after loading with LV@HPA/PEI-OVA, which increased significantly the cytokine IL-12 secretion and expression of surface molecules CD80 and CD86. Interestingly, DCs loaded with LV@HPA/PEI-DRibbles could promote the activation of tumor-specific T cells both in murine and in human T cells. In the following in vivo experiments, the vaccine of LV@HPA/PEI-DRibble-DCs significantly inhibited tumor growth and improved the survival rate of the PancO2 tumor-bearing mice.Conclusion: We established a high-performance anti-tumor vaccine of DCs loaded with LV@HPA/PEI nanoparticles and tumor-associated antigens in autophagosomes (DRibbles), which could serve as a therapeutic strategy in cancer immunotherapy.Keywords: aluminum hydroxide, antigen delivery, DRibbles, nano-adjuvant, cancer immunotherapy, autophagosome